Studies on the Derveni Papyrus Volume 2 - Most, Glenn W. 1952-; Janko, Richard 1955-; Piano, Valeria (Oxford Oxford University Press, Incorporated, 2022)
Studies on the Derveni Papyrus, Volume II brings together two new editions of the first fragmentarily extant columns of the Derveni Papyrus and seven scholarly articles devoted to their interpretation.
Cover -- Studies on the Derveni Papyrus -- Copyright -- Contents -- Notes on Contributors -- List of Illustrations -- 1. Black and White Plates (after p. 150) -- 2. Colour Plates (after p. 150) -- Figures -- List of Tables -- Abbreviations -- Introduction -- Part I: Two editions of the first columns -- 1: The Derveni Papyrus, Columns 41-7 (formerly I-VII): A Proekdosis from Digital Microscopy -- 1a. Methodology and Criteria of Reconstruction -- 1a.1 Techniques of Reading: Ink, Fibres, and Burning -- 1a.2 Techniques of Reconstruction: Stichometry, Bibliology, and Fibres -- 1b. Diplomatic Transcript and Palaeographical Commentary -- 1c. Text, Translation, and Apparatus Criticus -- 1d. Postscript -- 2: The Derveni Papyrus, Columns -2-VII: A Critical Edition from Digital Microscopy -- 2a. Methodology and Criteria of Reconstruction -- 2a.1 Preliminary Remarks -- 2a.2 From the Carbonized Roll at Derveni to Its Restoration by Anton Fackelmann -- 2a.3 Bibliometric and Bibliological Parameters of the Derveni Roll -- 2a.4 Reconstructing the First Columns: Structural Rules and Methodological Criteria -- 2a.4.1 Classification of G Fragments into (Small-)g and (Large-)G Fragments and Positioning of (Large-)G Fragments -- 2a.4.2 Size of Fr. G1 -- 2a.4.3 Methodological Principles -- 2a.5 Main Structural Features of the Edition -- 2a.5.1 Col. VII (47): Presence of Fr. F5a -- 2a.5.2. Col. VI (46): Absence of the Stichometric Sign and Conservation of the Traditional Numbering of Columns -- 2a.5.3 Col. IV (44): The New Placement of Fr. F17 -- 2a.5.4 Sovrapposti and Sottoposti to Frr. G5, G6, and G9 -- 2a.5.5 Col. III (43) -- 2a.5.6 The Columns Preceding Col. III (43) -- Cols. II-I (42-41) -- Col. 0 (40) -- Cols. -1 (39) and -2 (38) -- 2b. Diplomatic Transcript and Palaeographical Commentary -- Premise to the Edition -- Postscript.
Keywords: Derveni Papyrus; Derveni Papyrus; Derveni Papyrus; Manuscripts, Greek (Papyri); Manuscripts, Greek (Papyri); Manuscripts, Greek (Papyri); Conference papers and proceedings; Aufsatzsammlung